Implementasi Profil Pelajar Pancasila Dimensi Berakhlak Mulia di SD Negeri Mengkowo - M. Aziz Maghfuri; Agus Salim Chamidi (IAINU Kebumen, 2023)
The Pancasila Student Profile is the main goal of education developers in shaping student character. The purpose of this study is to analyze the implementation of the Pancasila Learner Profile at SD Negeri Mengkowo in improving student character education. This research uses. Data collection using observation, interview, and documentation techniques. The results of this study are to achieve the success of the implementation of the Pancasila Student Profile influenced by several factors including the role of the teacher, the vision and mission of the school, the role of the family, the role of the community, as well as awareness and self-motivation in students. If all the roles are supportive then the implementation of the Pancasila Student Profile can be maximized in the formation of children's character.